Alterações da função pulmonar e da força muscular respiratória em pacientes com sarcopenia primária - Furtado, Frederico Luiz Braz (2021)
Sarcopenia is characterized by progressive and generalized loss of skeletal muscle strength, accompanied by reduced muscle mass and adverse effects. The impact of sarcopenia on lung function and respiratory muscle strength, independent of the normal aging process, is currently not well understood. Objective: To synthesize the evidence obtained by comparing changes in pulmonary function in individuals with and without sarcopenia. Materials and methods: In November 2020, searches were conducted at PubMed, Embase and The Cochrane Library with a strategy related to sarcopenia, pulmonary function and respiratory muscle strength described in the supplementary documents (tables 1 to 3). Studies with individuals without respiratory disease and outcome for the effect of sarcopenia on pulmonary function and/or respiratory muscle strength were included; studies without the diagnosis of sarcopenia. The risk of bias was evaluated with the Newcastle-Ottawa Scale (NOS) version, adapted for cross-sectional studies. The difference of weighted means (WMD) of fvc (%) and FEV1 (%) with a 95% confidence interval was calculated. The random effects model was adopted with the Cochrane's Q test (P< 0.05) and the I2 test. Results: 5018 studies were found; 6 were selected for systematic review and 2 studies for meta-analysis. There was a reduction in FCV (%) in the group with sarcopenia, in relation to controls (WMD, -4.69; 95% IC, - 5,50 to -3,88; I2 = 1,48%). VEF1 (%) showed no difference between individuals with and without sarcopenia (WMD, -5.30; 95% IC, -14.39 to -3.80; I2 = 94.66%). Besides the small number of publications on the subject, there was a lack of detailed studies of pulmonary function, with measurements of total lung capacity, residual volume and mechanical characteristics of the respiratory system. Additionally, heterogeneity of methods and criteria for the diagnosis of sarcopenia was evident in this review, Conclusion: Primary sarcopenia compromises lung function, reducing the vital capacity of the elderly and, probably, causing a decrease in maximal respiratory mouth pressures.